CUSTOMER BEHAVIOUR IN THE AGE OF DIGITAL INSURANCE: A STUDY OF TRENDS, PREFERENCES, AND CHALLENGES - Jadav, Jayendrasinh (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study analyzes customer behaviour, trust, satisfaction, and perceived challenges in accelerating the use of digital insurance services among various demographic groups. The analysis, utilizing a sample of 300 respondents, investigates the impact of demographic factors—age, gender, occupation, education level, and income—on customer engagement, trust in data security, satisfaction with service speed, and perceived obstacles, including privacy concerns and technical challenges. Research demonstrates that digital insurance platforms have widespread appeal, with no notable demographic disparities in usage frequency or satisfaction levels, indicating a broadly positive opinion of digital services within the insurance industry. Privacy issues and technological obstacles surfaced as significant impediments to adoption, impacting all demographic groups uniformly. These findings highlight the necessity for comprehensive enhancements in data security and usability, enabling insurers to develop inclusive, dependable digital platforms that promote confidence and accessibility across their varied clientele. This research enhances comprehension of digital adoption within the insurance sector and offers practical recommendations for uniformly improving digital service quality.